An investigation into mentoring as a possible tool to alleviate practice shock among primary school educators in the context of curriculum 2005 - Rapuleng, Mahlomola Abel (University of the Free State (South Campus), 2002)
Once South Africa was democratized in 1994, it was discovered that the education system of the apartheid legacy failed to produce citizens who could compete internationally. It was also proved that the system was unable to develop essential human skills that would create jobs for all scholars at the end of their schooling career. For this purpose an Outcomes-Based Education (OBE) model for General Education and Training (GET) in South Africa, called Curriculum 2005 (C2005), was implemented since 1998. This sudden implementation ofa new curriculum in primary schools allegedly resulted in practice shock among the relevant educators with the result of many of them opting to leave the education profession. In light of these developments the researcher decided to undertake an investigation in order to establish whether the alleged practice shock indeed exists among these educators. The researcher also opted to investigate the feasibility of a mentoring programme for these educators as a possible solution for the problem of the apparent practice shock. The researcher then found it necessary to do a literature study on the following issues pertaining to the research problem: • The implementation of C2005 as an outcomes-based educational model in primary schools in S.A. • Practice shock as a possible consequence of the sudden implementation of the new curriculum; and • Mentoring of primary school educators as a possible tool to alleviate the alleged practice shock. The afore-mentioned literature study was subsequently supplemented by a case study survey among the educators of a selected primary school in the Ladybrand district. This case study survey took the form of a qualitative interview survey with selected educators at the primary school involved, qualitative observations of all the educators by the researcher (who also was the principal of the particular school) as well as a quantitative questionnaire survey among all the educators at the school. During the investigation possible problems experienced by the educators, the existence of practice shock among the educators as well as their views regarding mentoring as a possible tool to alleviate these problems and the emanating practice shock were investigated. On the basis of the data obtained during this investigation the researcher subsequently critically analysed and interpreted the data and eventually made the conclusion that the educators who took part in the project did indeed experience problems with the implementation of C2005; that practice shock was indeed a reality at the primary school involved; and that these educators were in fact of the opinion that a mentoring programme was a definite necessity. A number of recommendations regarding a mentoring programme for educators at primary schools were finally made.
Keywords: Mentoring/mentor/mentee; Practice shock; Primary education; General Education and Training (GET); Curriculum 2005 (C2005); Outcomes-Based Education (OBE); Curriculum implementation; Curriculum management; Human resource management; Educational management; Dissertation (M.Ed. (Postgraduate Education))--University of the Free State, 2002